The Effect of Origami Weaving Stimulation on the Fine Motor Skills of Children Aged 4–6 Years - Vinka Griselda Dhermawan; Dini Mariani; Novi Enis Rosuliana (Jurnal Keperawatan Olahraga, 2025)
Background: Fine motor development in early childhood plays a vital role in preparing children for academic activities and daily independence. Delays in this area can affect a child’s confidence and self-reliance. Aims: To examine the effect of weaving stimulation using origami techniques on improving fine motor skills in children aged 4–6 years. Methods: A pre-experimental one-group pretest-posttest design was employed, involving 31 children selected through total sampling from a kindergarten in Tasikmalaya. The intervention consisted of two 60-minute sessions focused on origami-based weaving activities designed to train hand-eye coordination, finger movement precision, and independence. The assessment instrument was a fine motor observation sheet developed by the researcher based on 10 indicators of early childhood development, using an interval scale of 1–4. Results: Statistical analysis showed a significant difference between pretest scores (mean 25.13 ± 1.54) and posttest scores (mean 36.77 ± 1.28), as indicated by the Wilcoxon Signed Rank Test (Z = -4.876; p = 0.000). Conclusion: These findings suggest that origami weaving stimulation is an effective and enjoyable approach to enhancing fine motor skills in young children. The study recommends integrating similar activities into early childhood education programs as a practical and engaging developmental stimulus